Improvement of microalgae lipid productivity and quality in an ion-exchange-membrane photobioreactor using real municipal wastewater - Haixing, Chang; Qian, Fu; Yun, Huang; Ao, Xia; Qiang, Liao; Xun, Zhu (International Journal of Agricultural and Biological Engineering, 2017)
To improve the productivity and quality of microalgae-based biodiesel when using municipal wastewater (MW) as nutrients source, an ion-exchange-membrane photobioreactor (IEM-PBR) was used in this study to eliminate the negative effects of pollutants in MW on microalgae Chlorella vulgaris and Scenedesmus obliquus. In the IEM-PBR, the real MW and microalgae cultures were separated in two chambers by the ion-exchange-membranes (IEMs). Nutrients (N, P, etc.) in the MW permeated into microalgae cultures through the IEMs, while pollutants (suspended solids, competitors, etc.) in the MW could hardly permeate into microalgae cultures. As a result, the lipid productivity in the IEM-PBR was improved to 85.7 mg/(L•d) for C. vulgaris and 111.8 mg/(L•d) for S. obliquus, which was slightly higher than that in the traditional photobioreactor (T-PBR) with real MW after centrifugation (82.5 mg/(L•d) for C. vulgaris and 105.8 mg/(L•d) for S. obliquus), but much higher than that in the T-PBR with untreated MW and primary MW (with lipid productivity of 20-30 mg/(L•d)). Besides, the lipid quality obtained in the IEM-PBR had higher proportion of cetane number (ca. 60%) and lower linolenic acid content (ca. 8%), which showed a superior quality in the IEM-PBR to that in the T-PBR. It demonstrated that the IEM-PBR is an effective approach to improve the productivity and quality of microalgae biodiesel. Keywords: microalgae, photobioreactor, lipid productivity, real municipal wastewater, ion-exchange-membrane DOI: 10.3965/j.ijabe.20171001.2706 Citation: Chang H X, Fu Q, Huang Y, Xia A, Liao Q, Zhu X. Improvement of microalgae lipid productivity and quality in an ion-exchange-membrane photobioreactor using real municipal wastewater. Int J Agric & Biol Eng, 2017; 10(1): 97－106.